DEVELOPMENT OF PHYSICS TEACHING INSTRUMENTS BELONG TO COOPERATIVE GROUP INVESTIGATION MODEL TO IMPROVE STUDENTS’ SELF-EFFICACY AND LEARNING ACHIEVEMENT - Tirta, Gusti Ayu Rai; Prabowo, Prabowo; Kuntjoro, Sunu (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This study aims to produce physics teachinginstruments with cooperative learning model type group investigation to improve students self-efficacy and learning achievement. Development of teachinginstrumentsusing Kemp model. The experimental design uses a one-pretest-posttest design model with three time replications. Subjects in this study are teachinginstruments and students of class XI MIPA. This research was conducted at SMA Negeri 3 Singaraja-Bali in the academic year of 2017/2018. Data were collected using validation method, questionnaire, observation, questionnaire and test. Data analysis techniques used are qualitative descriptive analysis and parametric statistical analysis. The results showed that the developed teachingintruments were valid, practical, and effective.The validitywas indicated by the average scores in a good categoryforlesson plan, BAS, student worksheet, achievement test and self-efficacy questionnaire.The practicisibilitywas showed by: (a) a good implementation of the lesson plan, (b) student activity is in excellent category, (c) the readability of BAS and student worksheet are in moderate categories, and (d) the obstacles during the learning activities can be overcome.The effectiveness was indicated by: (a) students? learning achievement has increased significantly; (b) students? self-efficacy has increased significantly; and (c) students respond is positive to the learning instruments and learning activity.  In conclusion, physics learning instruments with cooperative learning model type group investigation can be used to improve students? self-efficacy and learning achievement.